2022
DOI: 10.1002/prp2.1015
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life efficacy and safety of elexacaftor/tezacaftor/ivacaftor on severe cystic fibrosis lung disease patients

Abstract: Elexacaftor/tezacaftor/ivacaftor (ETI) is a cystic fibrosis (CF) transmembrane conductance regulator modulator, which has shown efficacy in CF patients (≥6 years) with ≥1 Phe508del mutation and a minimal function mutation. In October 2019, ETI became available on compassionate use basis for Dutch CF patients with severe lung disease. Our objective was to investigate safety and efficacy of ETI in this patient group in a real‐life setting. A multicenter longitudinal observational study was conducted to examine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The phase 3 trials reported a mean absolute increase in ppFEV1 of 14 points after 24 weeks of therapy with ELX/TEZ/IVA in pwCF with one p.Phe508del allele and a ppFEV1 of 40%–90% at baseline ( Middleton et al, 2019 ). A similar absolute increase in the ppFEV1 of 15% was observed in French, Dutch, and Belgian CF patients with advanced pulmonary disease (ppFEV1< 40% at baseline) ( Burgel et al, 2021 ; Kos et al, 2022 ; Stylemans et al, 2022 ). In a real-world, postapproval setting ELX/TEZ/IVA did not only significantly improve spirometry but also the lung clearance index as a measure of ventilation homogeneity ( Graeber et al, 2022b ; Stylemans et al, 2022 ).…”
Section: Pulmonarysupporting
confidence: 73%
“…The phase 3 trials reported a mean absolute increase in ppFEV1 of 14 points after 24 weeks of therapy with ELX/TEZ/IVA in pwCF with one p.Phe508del allele and a ppFEV1 of 40%–90% at baseline ( Middleton et al, 2019 ). A similar absolute increase in the ppFEV1 of 15% was observed in French, Dutch, and Belgian CF patients with advanced pulmonary disease (ppFEV1< 40% at baseline) ( Burgel et al, 2021 ; Kos et al, 2022 ; Stylemans et al, 2022 ). In a real-world, postapproval setting ELX/TEZ/IVA did not only significantly improve spirometry but also the lung clearance index as a measure of ventilation homogeneity ( Graeber et al, 2022b ; Stylemans et al, 2022 ).…”
Section: Pulmonarysupporting
confidence: 73%
“…There were no major safety concerns for pwCF and severe lung disease reported with use of IVA, TEZ/IVA, or ELE/TEZ/IVA 10–29 . Popowicz et al did note a transient yet significant decline in pulmonary function soon after initiation of full‐dose LUM/IVA that persisted for 24 hours; however, at 1 month, lung function returned to baseline for all pwCF 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, most therapeutic benefits were observed within 2–4 weeks after the start of ETI therapy and particularly beneficial effects were observed in peripheral zones of the lungs [ 52 ]. Another prospective, real-life study was performed by Kos and collaborators in a follow-up of 12 months [ 53 ]. Changes in ppFEV 1 , BMI, frequency of pulmonary exacerbations, and adverse effects were assessed in 20 PwCF carrying at least one copy of F508del-CFTR and advanced lung disease.…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%
“…Compared to baseline values, there were significant improvements at 12 months of ETI therapy in ppFEV 1 (mean increase of 13.7%), BMI (mean increase of 1.87 kg/m 2 ), CFQ-R score (mean increase of 32.3 points), and frequency of exacerbations (mean of 2.89 vs. 0.19, before and after ETI, respectively). Despite 55% of participants experiencing at least one therapy-related adverse event, these were mild to moderate in severity and no discontinuation of ETI therapy was required [ 53 ].…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%